How Immigration Reforms Affect Voting Behavior. (August 2018) - Abou-Chadi, Tarik; Helbling, Marc
This article investigates how changes in immigration policies affect migration as a vote-defining issue at upcoming elections. So far, the literature on issue voting has mostly focused on the role of issue entrepreneurs in politicizing new issues. In this article, however, we introduce policy change as a new potential determinant in the process of issue evolution. Moreover, in contrast to most of the literature that investigates the role of policy outcomes (such as economic growth or unemployment) on voting decisions, we analyze the effect of laws which can be directly attributed to governments and political parties. We focus on within-country variation and analyze national election surveys from the Netherlands, Denmark, and Germany between 1994 and 2011. These surveys include information on both self- and party-placements regarding immigration issues. To measure policy changes, we use data on immigration policies from the newly built Immigration Policies in Comparison dataset. While we expect a general reform effect, we investigate in more detail whether liberal and restrictive reforms have a similar effect on votes for left/right, government/opposition parties. It is shown that both liberal and restrictive reforms lead to increasing issue voting. While we show that government parties are not more affected than opposition parties, we see that party ideology partly plays a role.